(untitled) (INNOVATIVE ECONOMY, 2025)
Koliasa P.I., Bashutska O.S., Zavytii O.P. Innovative Pedagogical Approaches to Teaching Life Safety and Civil Protection in Vocational Education Institutions Purpose. The aim of this article is to provide a theoretical substantiation of innovative approaches to teaching life safety and civil protection in vocational education institutions and to determine their role for the formation of professional competence of future specialists. Methodology of research. The methodological basis of the study is a set of general scientific and special methods of cognition. Methods of analysis and synthesis were used to study scientific approaches to teaching life safety and civil protection and to determine their key characteristics. A systematic method was used to consider the preparation of vocational education seekers for safe activities as an integrated pedagogical system that combines cognitive, value-motivational, and behavioral components. Comparative analysis was used to compare traditional and innovative approaches to teaching safety-related disciplines. Generalization and abstraction made it possible to formulate theoretical conclusions regarding the feasibility of implementing constructivist, competency-based, risk-oriented, and axiological approaches. Theoretical modeling was used to substantiate the directions of modernization of teaching methods, taking into account the digitalization of the educational environment and the use of simulation and immersive technologies. Findings. The feasibility of modernizing the teaching of life safety and civil protection through the introduction of innovative pedagogical approaches, in particular the use of digital, simulation, and immersive technologies, gamification, microlearning, and the integration of safety cycle disciplines with professionally oriented subjects, has been substantiated. It has been proven that a comprehensive combination of cognitive, value-motivational, and behavioral components of training contributes to the formation of students’ readiness for activities in conditions of risk and uncertainty. It has been proven that the introduction of innovative pedagogical technologies contributes to increasing the effectiveness of professional training of students, forming their psychological readiness for activities in crisis situations, and developing information and digital competence. Originality. The systematization and theoretical generalization of innovative approaches to teaching security-related disciplines in vocational education institutions based on the integration of constructivist, risk-oriented, competence-based, and axiological approaches has been further developed. Practical value. The conclusions and generalizations obtained can be used in the development of educational programs, teaching and methodological support, and digital educational resources on life safety and civil protection, as well as in the process of improving the skills of teaching staff of vocational education institutions. Key words: life safety, civil protection, vocational education, safety culture, digitalization of education, innovative learning technologies, vocational education institutions.